Feedback-aided data acquisition improves myoelectric control of a prosthetic hand - Gigli, Andrea; Brusamento, Donato; Meattini, Roberto; Melchiorri, Claudio; Castellini, Claudio (Journal of Neural Engineering, 2020)
Objective. Pattern-recognition-based myocontrol can be unreliable, which may limit its use in the clinical practice and everyday activities. One cause for this is the poor generalization of the underlying machine learning models to untrained conditions. Acquiring the training data and building the model more interactively can reduce this problem. For example, the user could be encouraged to target the model's instabilities during the data acquisition supported by automatic feedback guidance. Interactivity is an emerging trend in myocontrol of upper-limb electric prostheses: the user should be actively involved throughout the training and usage of the device. Approach. In this study, 18 non-disabled participants tested two novel feedback-aided acquisition protocols against a standard one that did not provide any guidance. All the protocols acquired data dynamically in multiple arm positions to counteract the limb position effect. During feedback-aided acquisition, an acoustic signal urged the participant to hover with the arm in specific regions of her peri-personal space, de facto acquiring more data where needed. The three protocols were compared on everyday manipulation tasks performed with a prosthetic hand. Main results. Our results showed that feedback-aided data acquisition outperformed the acquisition routine without guidance, both objectively and subjectively. Significance. This indicates that the interaction with the user during the data acquisition is fundamental to improve myocontrol.
CRIS-Team Scopus Importer:2021-09-13
Keywords: Feedback guidance; Limb position effect; Myoelectric control; Online machine learning; Prosthetic hand; Training data acquisition